Obstacles to Using Cloud Accounting: Evidence from Kurdistan Region - Iraq - Hoshyar Abdulah Hawez, (QALAAI ZANIST JOURNAL, 2022)
The prevailing trend in the field of accounting recently is the use of cloud accounting or online accounting, because of its advantages, such as reducing cost and obtaining financial information in a timely manner and other advantages. The companies operating in Kurdistan region have begun to follow the example of international companies that rely on the cloud accounting system. Changing the accounting system to a cloud accounting system faces some difficulties and obstacles, just like any other changes within the company. The main objective of this research is to identify the concept of cloud accounting and whether there are obstacles facing this change in the Kurdistan region and to put forward some opinions on how to overcome these obstacles. The research found that there are many obstacles that hinder the process of implementing and using cloud accounting system in Kurdistan Region.